Jinx's magic - Blackwood, Sage (Harper, 2014)
"A young wizard's apprentice, Jinx, learns that his forest home, the Urwald, is under threat, and to save it he must travel to a new land"..
Sequel to: Blackwood, Sage: Jinx
Keywords: Magic; Wizards; Orphans; Forests and forestry; Fantasy; Jugendbuch